Tax Collection Authority for Hotels Aboard Tourist Boats After Law Number 1 of 2022 and Law Number 7 of 2021 - Hendra Kurniawan; Emir YusufInspiration; Tia Rizkya DilbarSumadi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
ABSTRACT This research was conducted with the aim to find out how the regulations related to the authority to collect taxes on hotels on board tours after the issuance of the HKPD Law and HPP Law. Taxes on hotels aboard tour boats so far have created a separate polemic regarding the authority of the tax collection agency authorized to collect this type of tax, namely, whether it is a Regional Tax which is the authority of the Regional Government or is it the Center which is the authority of the Central Government, this is because there is an object that is the same wedge between the hotel tax on the tour boat and the VAT on the tour ship itself. Where in Law Number 28 of 2009 it has not been specifically regulated regarding whether staying on a tour boat is part of the hotel tax. For hotels on board tours it is more appropriate to be collected by the Regional Government. In the preparation of laws related to local taxes in the future, to include hotel tax coverage from a more substantive point of view and includes the nature of the accommodation services business itself, which in the future will likely be very transformative, not only on ships, but also by train, car and other modes, for this reason, it is better not to be limited by a limited scope.